Managing smart work systems and their impact on developing workers capabilities in light of digital transformation - AL-Rasheed, Areej Ali Hussein (Edelweiss Applied Science and Technology, 2025)
The main aim of this study was to investigate how managing smart work systems impacts the improvement of employee skills within Iraqi telecommunication companies amidst the digital transformation era. The study utilized the independent variable associated with managing smart work systems alongside the variable encompassing diverse skills (creative, cognitive, digital, and artistic), employing a descriptive analytical methodology. A cross-sectional survey was directly administered to 153 male and female employees working in the IT and HR departments of ITC. This study highlighted the intersection of information and human resources management within these organizations. Conducting statistical analysis using the SPSS program and employing multiple linear regression and hierarchical regression equations, the study uncovered several noteworthy findings. It was noteworthy that smart work systems management had a significant impact on improving employee capabilities within ITC. Additionally, the study identified the moderating role of digital transformation in the relationship between smart work systems management and employee skills, including creative abilities. Based on these results, the study suggests that ITC prioritize support for the information systems they utilize to improve data flow and facilitate effective information exchange.